Service Robots, the Innovation of Our Era: A Qualitative Research in the Tourism Sector - Yildiz, Bülent; Çavdar, Ertuğrul; Kütahyali, Dilber Nilay (Yunus TOPSAKAL, 2022)
Today, robots are widely used in service and manufacturing operations. Service robots are becoming more and more popular in the tourism sector. Therefore, there is a growing body of research on consumer perceptions and expectations of service robots. This study also investigated consumers' views of service robots in the tourism sector. The sample consisted of 787 participants. Data were collected online using a survey. The data were analyzed using MAXQDA. The results revealed nine dimensions: emotion, standardization, time, social impact, convenience, communication, impact on the workplace, technical problems, and assurance. The dimension of emotion consists of ten subdimensions: understanding emotions, apathy, sincerity, interaction, problematic interaction, personalized service, body language, attractiveness, irritability, and the privilege of being a human. The dimension of "standardization" consisted of seven subdimensions: reliability, defined job, quality, monotony, patience, practicality, and equality. The dimension of "time" consisted of two subdimensions: speed and timeliness. The dimension of "social impact" consisted of six subdimensions: unemployment, social communication, adaptation problems, financial problems, social problems, and technology dependence. The dimension of "convenience" consisted of four subdimensions: facilitating, workload, flexibility, and safety. The dimension of "communication" consisted of four subdimensions: understanding, foreign languages, informing, and comfort. The dimension of "impact on the workplace" consisted of five subdimensions: efficiency, cost, experience, suitability for the workplace, and workforce stability. The dimension of "assurance" consisted of four subdimensions: health, danger, trust, and information security.
Keywords: Turizm (Diğer); Tourism (Other); robot technology; tourism industry; service robots; 9. Industry and infrastructure; 8. Economic growth